The Diary of My Emotions: Recognizing and Supporting Emotional Wisdom of Children from Economically Underresourced Communities - Carrillo-Carrillo, Sonia Patricia; Navarro-Arana, Cristian Edgardo (Journal of Childhood Studies, 2026)
This paper presents a reflective account of the implementation of The Diary of My Emotions, a pedagogical project designed to support and highlight the existing emotional competencies in a preschool classroom in an economically underresourced context. Grounded in critical childhood studies and postdevelopmental approaches, the initiative engaged children and their families in co-constructing emotional understanding through multimodal literacy, embodiment, and the visualization of their peer culture, which evoked their existing emotional skills and cultural knowledge making. Despite challenges such as time constraints and initial family resistance, the project contributed to a more inclusive and emotionally supportive educational environment.